Crack sliding model for non-shear FRP-reinforced slender concrete elements under shear - El-said, Amr; Awad, Ahmed; El-Sayed, Taha A.; Özkılıç, Yasin Onuralp; Deifalla, A.; Tawfik, Maged (Frontiers in Materials, 2023)
Fiber-reinforced polymer (FRP)-reinforced concrete (RC) elements fail under one-way shear in a devastating and complicated manner with no adequate warning. In recent decades, there has been pioneering research in this area; however, there is no agreement among researchers regarding mechanically-based models. Thus, in this current study, a plasticity-based model is developed for FRP-RC elements under shear. A selected model was firstly assessed for its accuracy, consistency, and safety against an extensive experimental database. Secondly, a plasticity-based model (i.e., crack shear sliding model) was adapted, refined, and proposed for FRP-RC elements under one-way shear. The two proposed models were found to be reliable and more accurate with respect to selected existing methods. Modeling of FRP’s axial rigidity is more consistent only under Young’s modulus with respect to the experimental database. Several concluding remarks on the selected existing models are outlined and discussed to assist the future development of these models and design codes.